Developing “D-A-M-E Model” For Analyzing Multifaceted Creative Communication Process In Artificial Intelligences (AI) Era - Agustina Kusuma Dewi; Adi Surahman (Kartala Virtual Studies, 2026)
Abstract Complex layers of words—images in mixed media culture has changed social norms; also the communication process. The AI era has raised the cultural gap, changing the meaning of art and design in a historical context. Although, certain cases in popular culture break this pattern, offering a timeless aesthetic appeal that transcends generations. One of them is music video "70 Million" by Hold Your Horses!’s band (2011)—offering revolutionized conventional pop-rock music videos, inserting a new dimension into them—making art history education that is often seen as dry, bored, and uninteresting—become something carried fresh knowledge; even in parody. Using symbolic interpretive approach with textual analysis, this article analyse the iconic translation and its relevance context in the music video; this research also develops the D-A-M-E (Decoding–-Adaptation/Adoption & Modification—Encoding) Model as a theoretical framework. Becoming medium communication, song combined with the music video has the potential to become creative media that brings message timeless—closely related to ideology and the creator's vision. This music video breathes new life into art history, using collage as one style of its translation visual icon of art history—making it fresh, vibrant, challenging perceived banality—until now, in the AI era. Keywords: translational analysis, artificial intelligence, collage, iconic image, cultural banality, art history, media education